Implementasi Penilaian Afektif pada Proses Pembelajaran IPS di SMP Negeri 6 Ambon - Manuhuttu, Silvia; Sahusilawane, Stevie (Jurnal Pendidikan Ekonomi, 2024)
Affective assessment plays a vital role in shaping student attitudes but is often neglected in practice because teachers predominantly focus on cognitive aspects. This study aims to describe the implementation of affective assessment in social studies learning at SMP Negeri 6 Ambon. A qualitative approach with descriptive methods was employed, utilizing observation, in-depth interviews, and document analysis of lesson plans and assessment instruments. The main findings indicate that affective assessment planning exists in lesson plans but is limited to observational sheets used by teachers. Students' spiritual and social attitudes were generally good, evident through prayer, greetings, cooperation, discipline, responsibility, and communication skills during group discussions. This research provides an in-depth description of the relationship between affective assessment planning and its actual implementation. The implications suggest a need for teacher training in developing comprehensive affective assessment instruments, and it is recommended that schools facilitate improving teachers' competencies to implement affective assessments consistently and comprehensively